A STUDY: CORRELATION AMONG ENGLISH READING HABIT, INTERPERSONAL INTELLIGENCE AND READING COMPREHENSION ABILITY - putra, Reko Hary; Sinthya Pralinda; Hasrinal (JR-ELT (Journal of Research in English Language Teaching), 2025)
The purpose of this study was to examine the relationships between English reading habits, intrapersonal intelligence, and students’ reading comprehension ability. A quantitative approach with a descriptive correlational design was employed. The participants consisted of 44 fourth-semester students of the English Department at IAIN Kerinci selected through total sampling. Data on English reading habits and intrapersonal intelligence were gathered using questionnaires, while a reading comprehension test measured students’ reading performance. The data were analyzed using Pearson Product Moment correlation and multiple linear regression.The findings revealed a very strong and significant correlation between English reading habits and reading comprehension (r = 0.867, p < 0.05). Intrapersonal intelligence also showed a fair and significant correlation with reading comprehension (r = 0.576, p < 0.05). Simultaneously, English reading habits and intrapersonal intelligence demonstrated a very strong and significant combined relationship with reading comprehension (R = 0.868). The adjusted R² of 0.741 indicates that both predictors contributed 74.1% to the variance in reading comprehension. Regression analysis further showed that English reading habits significantly predicted reading comprehension, whereas intrapersonal intelligence did not.